Pendampingan Pembelajaran Interaktif dalam Penguatan Karakter Religius Siswa di MA Nurul Huda Sedati Sidoarjo - Laila Badriyah; Siti Kholidatur Rodiyah; Masfufah Masfufah; Mufaizah Mufaizah (Program Studi Manajemen FEB UNM, 2026)
Islamic schools (madrasahs) play a strategic role not only in fostering students’ academic achievement but also in cultivating religious character as an essential foundation for navigating contemporary social challenges. However, learning practices that remain predominantly teacher-centered often limit student engagement, reducing opportunities for the meaningful internalization of religious values. In response to this issue, this community service program aimed to facilitate the implementation of interactive learning to enhance student participation and strengthen religious character among students at MA Nurul Huda Sedati Sidoarjo. The program employed a Participatory Action Research (PAR) approach involving four stages: observation, planning, action implementation, evaluation, and reflection, with active collaboration between teachers and students throughout the process. Interactive learning strategies were implemented through group discussions, presentations, question-and-answer sessions, and contextual reflective activities integrated with religious values. The findings revealed a significant transformation in the learning process toward a more participatory, dialogic, and reflective environment, as evidenced by increased student involvement in discussions, greater confidence in expressing ideas, and improved collaborative skills. Furthermore, the program contributed to strengthening students’ religious character, reflected in the development of discipline, responsibility, mutual respect, and social awareness within classroom interactions. These findings indicate that interactive learning serves not only as an effective approach for enhancing student engagement but also as a meaningful medium for internalizing religious values and translating them into everyday attitudes and behaviors. Therefore, interactive learning assistance grounded in religious values can be considered a strategic and sustainable approach to supporting character education within the madrasah context.